ANTIOXIDANT AND THERMAL PROPERTIES OF ZN(II), FE(II), AND MN(II) COMPLEXES WITH THIOPHENE-CARBOXYLATE LIGAND: SYNTHESIS AND CHARACTERIZATION" - Aydın, Mehmet Can; Kaya, Esra Nur; Yılmaz, Burak Emre (Global Journal of Chemistry, Biology and Physics (GJCBP), 2023)
Schiff-base ligands featuring heterocyclic moieties and heteroatoms such as N, O, and S have garnered significant attention in the realm of chemistry and biology due to their diverse biological activities and their remarkable interactions with transition metal ions. These complexes have been identified as effective and stereo-specific catalysts for a range of chemical reactions, including oxidation, reduction, and hydrolysis, while also exhibiting substantial biological potential. The current review explores the multifaceted applications of Schiff-base complexes derived from both transition and non-transition metals, shedding light on their role as promising materials for various catalytic, sensing, and medicinal applications.